The Far Northwest:Sutherland, Assynt and Coigach - Bradwell, Tom; Ballantyne, Colin K. (Springer Science and Business Media B.V., 2021)
The far northwest of mainland Scotland is renowned for its scenery, structural complexity and geodiversity, and is designated as a UNESCO Global Geopark. The region is bisected by the Moine Thrust Zone (MTZ), west of which a foreland of undeformed Archaean gneiss supports inselbergs of Neoproterozoic and Palaeozoic rocks, and east of which are thrust-stacked, deformed metasedimentary rocks of the Neoproterozoic Moine Supergroup. The MTZ forms a north–south belt within which rocks were extensively thrust and folded during the Caledonian Orogeny. Successive Pleistocene glaciations have resulted in an array of erosional landforms: troughs, rock basins, cirques, glacially steepened inselbergs, extensive areas of knock-and-lochan terrain and clusters of glacial megagrooves. During the last and earlier ice-sheet glaciations, the region sourced northwestward-flowing ice feeding the Minch Ice Stream, which extended far across the adjacent shelf, but by ~15 ka the last ice sheet had retreated to its mountain heartland. The Loch Lomond Stade (~12.9 to 11.7 ka) witnessed reoccupation of the main mountain axis by a substantial (~350 km 2 ) icefield, and cirque glaciers formed on peripheral mountains; the extent of the former is mainly delimited by multiple recessional moraines, the latter by end-moraine belts. Lateglacial and Holocene landforms include outwash or delta terraces at fjord heads, sea stacks, beaches backed by sand dunes, rock-slope failures, relict talus accumulations, and active periglacial and aeolian features on high ground. Karst terrain developed on dolostones comprises sinkholes, resurgences and extensive cave networks formed by water-table lowering due to Middle and Late Pleistocene valley deepening.